Student's Perspective on The Implementation of The Project Based Learning (PJBL) Method in Project Management Courses During The Covid-19 Pandemic - Wahyu Nofiantoro; Nisa Ismundari Wildan (Universitas Terbuka, 2022)
The implementation of practicum courses using online methods at the Universitas Indonesia during the pandemic has its own challenges. The entire learning process is carried out online, both synchronously and asynchronously. In the project management practicum course, the Project Based Learning (PjBL) method is used as a learning strategy, at the end of the courses students are assigned to make a final project related to the development of vocational education. The purpose of this study was to evaluate the implementation of the PjBL method in Project Management Practicum courses conducted online during the COVID-19 pandemic in the 2020-2021 academic year at the Secretarial Office Administration Study Program, Vocational Education Program, Universitas Indonesia. The research subjects were 21 students, using quantitative methods, with data collection techniques using questionnaires using total sample as sampling technique. From the results of this study indicate that the PjBL Learning model was responded very well and good by 91.6% of students, with the dimensions of teacher interaction by 91.6%, increasing motivation by 77.6%, understanding of learning materials by 94.7%, critical thinking by 100%, time management by 92%, learning outcomes by 96.5%, Course suitability by 90%. The conclusion of this study, the PJBL method which was implemented through online during the pandemic in the project management practicum course was quite effective, especially in sharpening students' critical thinking skills and achieving good learning outcomes.